Comparative study between eras protocol and conventional perioperative care in elective cesarean section patients in a tertiary care centre of eastern India: 10.55131/jphd/2023/210308 - Sravani, Poreddy; Pravalina, Rachita; Sahoo, Gitanjali; Pati, Basanta Kumar (Journal of Public Health and Development, 2023)
Enhanced Recovery after Surgery (ERAS) was originally introduced in colorectal surgery. ERAS pathways have been extensively implemented in various surgical branches like orthopedics, urology, and gynecologic surgery. Commencement of these ERAS programs has consistently resulted in a decreased duration of hospital stay and enhanced patient comfort. We aim to implement the ERAS program successfully with the main objective of comparing the duration of hospital stay in both groups. A prospective comparative observational study was conducted at the Department of Obstetrics and Gynecology, in a tertiary care center of Bhubaneswar. Non-probability convenient sampling was done and consenting patients undergoing elective cesarean sections were included in the study conducted over 1.5 years. 200 pregnant women were included in the study. 100 were enrolled in the ERAS group and 100 in the conventional peri-operative hospital protocol group. None of the participants were lost to follow-up in either group. Post-operative outcomes in both groups were analyzed. In the study, there was a significant difference in the mean duration of 1st oral intake, 1st appearance of bowel sounds, first ambulation, catheter removal, 1st passage of flatus, bowel movements and postoperative length of stay between the two groups. The application of the ERAS protocol in our hospital led to a shorter duration of hospital stay postoperatively. Early allowance of oral diet reduced the duration of appearance of 1st bowel sounds, the first passage of flatus, and bowel movements. It also helped in ambulating the patients early, early catheter removal and faster resumption of regular normal diets. We recommend the application of the ERAS protocol to all uncomplicated cesarean sections. ERAS implementation challenges can be overcome by education of patients and care givers along with communication of economic benefits of ERAS to health care administrators.